Food Processing and Learning Interests of Class XI Students at SMK BPP Bandung - Arnely Renata; Tati Setiawati; Ai Mahmudatussadah (Universitas Pendidikan Indonesia (UPI), 2022)
This research was motivated bythe low achievement of the average score of the Continental Food Processing subject is still below the KKM, namely out of 37 students a total of 5 students got high scores (80-100), 12 students got moderate scores (60-75), 8 students got low scores ( 50) and 12 students scored less (50). This is because they have not mastered the material that has been taught by the teacher in learning in class, so that students do not have enough provisions to understand the next activity in carrying out learning activities. This can cause students to lack interest in learning. This study aims to determine student learning difficulties, student learning interest and the correlation between learning difficulties and student learning interest in Continental food processing at SMK BPP Bandung. The research method used is descriptive correlational. The population in this study were all students who received the Continental Food subject in class XI and XII at SMK BPP Bandung, totaling 101 people with a sample of 81 people calculated based on the Taro Yamane formula using the Proportionate Stratified Random Sampling technique. The data collection technique used a closed questionnaire with a Likert scale with data analysis using descriptive analysis and Rank Spearman correlation. The results of the analysis show that students' learning difficulties are high when it comes to theory and practice of continental food processing at SMK BPP Bandung, student learning interest is low when it comes to theory and practice of Continental food processing at SMK BPP Bandung.